A telling society: Reflections on the Trent Archives of Popular Writing - Antonelli, Quinto (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
Thanks to its deep local roots, the Trento Archive of popular writing has a very particular history. First, it assumed the functions of an “anti-archive” (collecting and preserving writing by the subordinate social classes), while continuing to preserve the memory of the Italian minority in the times of the Habsburg Empire. Later, it welcomed small family archives containing much writing related to the home (mostly peasant). And finally, thanks to the deposit of letters from admirers of the singer Gigliola Cinquetti, it has become an archive of national importance, surpassing the connotative definition of “popular” in the quality of the writing collected.
Keywords: writing; archives; minorities; farmers